Pulsed cooperative backward emissions from non-degenerate atomic transitions in sodium - Jonathan V Thompson; Charles W Ballmann; Han Cai; Zhenhuan Yi; Yuri V Rostovtsev; Alexei V Sokolov; Phillip Hemmer; Aleksei M Zheltikov; Gombojav O Ariunbold; Marlan O Scully (New Journal of Physics, 2014)
We study backward cooperative emissions from a dense sodium atomic vapor. Ultrashort pulses produced from a conventional amplified femtosecond laser system with an optical parametric amplifier are used to excite sodium atoms resonantly on the two-photon 3S $_{1/2}$ –4S $_{1/2}$ transition. Backward superfluorescent emissions (BSFEs), both on the 4S $_{1/2}$ –3P $_{3/2}$ and 4S $_{1/2}$ –3P $_{1/2}$ transitions, are observed. The picosecond temporal characteristics of the BSFE are observed using an ultrafast streak camera. The power laws for the dependencies of the average time delay and the intensity of the BSFEs on input power are analyzed in the sense of cooperative emission from nonidentical atomic species. As a result, an absolute (rather than relative) time delay and its fluctuations (free of any possible external noise) are determined experimentally. The possibility of a backward swept-gain superfluorescence as an artificial laser guide star in the sodium layer in the mesosphere is also discussed.